Актуальні тенденції у SMM як детермінанти формування стратегій українських брендів - Гевко, Соломія; Вовк, Наталія (Видавництво Львівської політехніки, 2025)
The article explores current trends in the field of social media marketing (SMM), which play a key role in shaping effective strategies for promoting brands and business pages in the digital environment. The focus of the analysis is on the latest trends that contribute to increasing brand awareness, actively engaging the target audience, and strengthening interaction between the company and the consumer in social networks. The main criteria for successful trending content are highlighted.
Keywords: контент; тренди; Socisl Media Marketing; соціальні мережі; впізнаваність